PENETAPAN KADAR VITAMIN C LIMBAH KULIT BUAH APEL MANALAGI (Pyrus malus L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - A. Muflihunna; Adli Dzil Ikram; Sukmawati Sukmawati (As-Syifaa Jurnal Farmasi, 2022)
Vitamin C is a vitamin that is water soluble and one vitamin that is needed by the body. To meet the intake of vitamin C needed source of vitamin a derived from fruits, one of which is Appel Part of the appel , which is still rarely used is its skin. Apple peel is very beneficial for health however the situation is only considered as waste that has not been utilized well. This study aims to determine the levels of vitamin C on the skin of the Apple (Pyrus mallus L)  by the method of spectrofotometry uv-visible wavelength 243 nm. This research uses experiments with purely research stage comprised sample preparation, qualitative test, making the solution of the parent raw, quantitative test, determination of wavelength of maximum vitamin and creation of calibration surve. Based on the research that has been done, the result of the qualitative test to prove the presence of high content of vitamin C contained in appel peels, with the highest level obtained in the skin of the plantain by 13,534 mg/g extract